THE IMPACT OF BREAKFAST SKIPPING ON TYPE 2 DIABETES RISK AMONG UNIVERSITY STUDENTS IN KARACHI" PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
Objectives: This study aims to investigate the impact of breakfast skipping on the risk of developing Type 2 Diabetes Mellitus among university students in Karachi, Pakistan.Background: In recent years, several studies have suggested a strong link between skipping breakfast and an increased risk of obesity, overweight, and subsequently Type 2 Diabetes Mellitus. Skipping breakfast may lead to poor metabolic regulation, higher body mass index (BMI), and insulin resistance, which are significant risk factors for diabetes. Understanding these patterns among young adults is crucial for implementing effective health-promoting interventions. This study builds upon previous research by examining the behavior and consequences of breakfast skipping in a university student population.Study Design: Cross-Sectional StudyStudy Setting: It was Conducted at the Department of Community Health Sciences of Bahria University of Health Sciences, Karachi.Study Duration: November 2022 – April 2023Methodology: A sample size of 384 was calculated using Epi-info, with a 95% confidence interval and a 5% margin of error. A random sampling method was employed. Data were analyzed using IBM SPSS Statistics 23. Linear regression was applied to assess the association between breakfast skipping and the risk of developing Type 2 Diabetes. A p-value of